The Influence of In Vitro Degradation on the Properties of Polylactic Acid Electrospun Fiber Mats - Kardo Khalid Abdullah; Kolos Molnár (Fibers)
The scope of our study was to investigate the changes in electrospun polylactic acid (PLA) fiber mats’ morphological, mechanical, and thermal properties in vitro. We electrospun two sets of PLA fiber mats with different average diameters, E6 (747 nm) and E10 (1263 nm). The degradation study of PLA electrospun fibers was carried out in phosphate-buffered saline solution at 37 °C to simulate conditions within the human system. The results reveal the thicker fibers (E10) degraded more rapidly than the E6 sample due to their different morphology. E10 showed a 29% reduction in diameter and a 41% weight loss, while E6 exhibited an 18% reduction in diameter and a 27.5% weight loss. E6’s Young’s modulus increased by 3.55 times, while E10’s rose by 2.23 times after 28 days of degradation, and the fibers became more rigid. E6 showed a more pronounced decrease in crystallinity compared with E10. Changes in electrospun fiber diameters and crystallinity greatly influence the degradation mechanism of PLA.